2006
DOI: 10.1103/physrevlett.96.095301
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of a Long Electronic Spin Relaxation Time of Cesium Atoms in Superfluid Helium

Abstract: The longitudinal electronic spin relaxation time of Cs atoms optically polarized in superfluid helium (He II, 1.5 K) has been measured with special care to cope with a serious decrease in the number of Cs atoms in the observation region. This decrease, mainly caused by helium convection in introducing the atoms into He II by laser sputtering, was significantly reduced using a new atom implantation method. Combined with a careful correction for the number of atoms, we have determined the relaxation time to be 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The original optical pumping experiments [123] on Rb and Cs in superfluid helium did not determine the corresponding T 1 time. It was only recently that a careful determination of Cs in HeII was obtained by Furukawa et al [194] who determined a lower bound of T 1 = 2.24 (19) s in a field of 500 μT. This relaxation time is approximately two times longer than the T 1 time in solid 4 He which we have determined to be T 1 ≈ 1 s in external magnetic fields ranging from 10 nT to 100 μT [187].…”
Section: Relaxation Timesmentioning
confidence: 44%
“…The original optical pumping experiments [123] on Rb and Cs in superfluid helium did not determine the corresponding T 1 time. It was only recently that a careful determination of Cs in HeII was obtained by Furukawa et al [194] who determined a lower bound of T 1 = 2.24 (19) s in a field of 500 μT. This relaxation time is approximately two times longer than the T 1 time in solid 4 He which we have determined to be T 1 ≈ 1 s in external magnetic fields ranging from 10 nT to 100 μT [187].…”
Section: Relaxation Timesmentioning
confidence: 44%
“…Surprisingly, T 1 times superior to that of alkali atoms in either solid [16,17] or superfluid [19] helium were observed at densities many orders of magnitude higher. Parahydrogen shows results competitive with what has been achieved with NV centers and phosphorous donors in silicon, with the potential for improvement and the possibility of working with a wide variety of dopant atoms.…”
mentioning
confidence: 94%
“…The properties of impurities (atoms, molecules, ions, electrons) in helium (superfluid helium, solid helium, nanodroplets, and so forth) can be applied not only to the study of atomic phenomena [5][6][7][8] but also to several fields of research [9][10][11][12] such as fundamental physics, spin properties, and quantum computing. Since the pioneering work on the optical pumping of atoms in superfluid helium (He II) by implanting atoms into He n by a laser sputtering method [5], laser spectroscopy measurements of various atomic species in a helium have been carried out intensively to clarify spectral and spin properties and to study magnetic resonance spectra [7,8,13,14], * y angxf @ ribf.riken.jp Our interest in the laser spectroscopy measurement of various atomic species was sparked by the confirmation of the greatly broadened (10 nm) and blue-shifted (>15 nm) absorption line spectrum [15] of atoms and the successful optical pumping of Rb and Cs atoms in He II [14]. In recent years, our group has been studying spectral and spin properties for a variety of atomic species in He II [16,17], The initial work by Furukawa et al [13] confirmed the long relaxation time (>2 s) as well as the long residence time of Cs atoms in He II, which enabled us to obtain a deeper understanding of the spin relaxation mechanism and perform high-resolution magnetic resonance experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work on the optical pumping of atoms in superfluid helium (He II) by implanting atoms into He n by a laser sputtering method [5], laser spectroscopy measurements of various atomic species in a helium have been carried out intensively to clarify spectral and spin properties and to study magnetic resonance spectra [7,8,13,14], * y angxf @ ribf.riken.jp Our interest in the laser spectroscopy measurement of various atomic species was sparked by the confirmation of the greatly broadened (10 nm) and blue-shifted (>15 nm) absorption line spectrum [15] of atoms and the successful optical pumping of Rb and Cs atoms in He II [14]. In recent years, our group has been studying spectral and spin properties for a variety of atomic species in He II [16,17], The initial work by Furukawa et al [13] confirmed the long relaxation time (>2 s) as well as the long residence time of Cs atoms in He II, which enabled us to obtain a deeper understanding of the spin relaxation mechanism and perform high-resolution magnetic resonance experiments. Subsequently, making use of the broadened absorption spectra and long spin relaxation time of atoms in He II, sufficiently large atomic and nuclear polarization was achieved by optical pumping of stable alkali-metal atoms (Rb, 50%; Cs, 90%) as well as non alkali-metal atoms (Ag and Au, 85%) [18].…”
Section: Introductionmentioning
confidence: 99%